O tripé da alfabetização: consciência fonológica, princípio alfabético e letramento - Scherer, Ana Paula Rigatti (2020)
This article deals with the teaching reading and writing tripod: phonological awareness, explanation of the alphabetical principle and literacy. Rigatti-Scherer’s research (2008) presents evidence regarding the three guiding axes. Are they: developing phonological awareness throughout the literacy period provides the learning of writing more effectively and that, being established, provides better performance in phonological awareness; the explanation of the alphabetical principle during the teaching reading and writing period facilitates the learning of writing for students of regular classes and students with special needs; literacy enables interaction and the real use of reading and writing functions. The balanced three “feet” support teaching reading and writing.